Steam reforming of acetic acid using Ni loaded activated carbons obtained from biomass residues. - Cabrera-Reyes, Paula; Rivas-Márquez, María Nerea; Riquelme-García, Paula; Ruiz-Rosas, Ramiro Rafael; Navlani, Miriam; Rosas-Martínez, Juana María; Cazorla-Amorós, Diego; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2026)
Steam reforming (SR) of oxygenated compounds in the pyrolysis liquids of biomass residues represents a sustainable path for renewable hydrogen generation. It can be carried out by using nickel catalysts supported over activated carbons (ACs) obtained from the same residues, which enhances the sustainability of the process. The aim of this work consists of the study of the effect of the catalytic support on the performance of nickel catalysts in the SR of acetic acid (AA) as model compound.
Keywords: Carbón activado; Níquel; Catalizadores; Steam reforming; Nickel; Activated carbon